ANALISIS PENERAPAN TARIF PROGRESIF TERHADAP PERTUMBUHAN WAJIB PAJAK KENDARAAN BERMOTOR DICABANG PELAYANAN DINAS PENDAPATAN DAERAH PROVINSI WILAYAH KOTA BANDUNG - Winarso, Widi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
This study aims to find out how much the application of progressive rates branched provincial revenue department service area of the city of Bandung II kawaluyaan , how much growth taxpayer branched motor vehicle services Dipenda province of the city of Bandung ii kawaluyaan , how much change in the application of progressive tax rates and the growth of mandatory branched motor vehicle tax services Dipenda province of Bandung city kawaluyaan II . The method used is descriptive analysis kuantitatif.Teknik approach to data collection is done through data obtained directly from the data source where the study was conducted branched provincial revenue department service area of the city of Bandung II kawaluyaan and literatur.Tekhnik Analysis of data from multiple data used is the using descriptive analytical techniques namely troubleshooting procedures studied by exposing the data obtained from interviews , literature , and observations , then analyzed and conclusions drawn . By using this technique the author will give an overview of the issues discussed with the facts and the data that is branched provincial revenue department service area of the city of Bandung II kawaluyaan . The results showed that the application of progressive rates on the growth of the motor vehicle tax payers to change at the time of application of progressive rates is by decreasing the growth of motor vehicle taxpayers are branched . Keywords: growth of taxpayers motor vehicles, progressive rates